Overexpression of miR‐17 in gastric cancer is correlated with proliferation‐associated oncogene amplification. (July 2014) - Park, Dongmin; Lee, Seok Cheol; Park, Jun Won; Cho, Soo Young; Kim, Hark Kyun
<x xml:space="preserve">Abstract</x> The molecular mechanism underlying microRNA (miR)‐17 overexpression has not been clearly evaluated in gastric cancer. We aimed to evaluate the functional roles of miR‐17 in gastric cancer and test its viability as a therapeutic target. We conducted comparative genomic hybridization and expression array analyses on human gastric cancer tissue samples, as well as evaluating the functional roles of miR‐17 in gastric cancer cell lines and transgenic mice. miR‐17 overexpression in gastric cancer patients was associated with copy number gain of proliferation‐associated oncogenes such as MYC, CCNE1, ERBB2, and FGFR2. Copy number gain of MIR17HG gene (13q31.3) was rare, with an overall frequency of 2% in gastric cancers (1 of 51). miR‐17 knockdown suppressed the monolayer and anchorage‐independent growth of FGFR2‐amplified KATO‐III gastric cancer cells. mir‐17–92 TG/TG mice overexpressing the mir‐17–92 cluster under the villin promoter developed spontaneous benign tumors in the intestinal tract (log‐rank P for tumor‐free survival = 0.069). Taken together, miR‐17 overexpression in gastric cancer was rarely associated with MIR17HG gene amplification, but correlated with proliferation‐associated oncogene amplification. Therefore, miR‐17‐targeting approach may benefit patients with gastric cancers harboring proliferation‐associated oncogene amplification.